PENGABDIAN MASYARAKAT UNTUK PENCEGAHAN STUNTING DI SEKOLAH TAHFIDZ RAUDHATUL QUR’AN, MALANG - Kadji, Dzuliyati; Pangestuty, Farah Wulandari; Santoso, Dwi Budi; Wijaya, Asyadia Haq Zahra (Universitas Mataram, 2024)
Undernourishment is an enormous health issue in Indonesia. Younger children are more likely to be stunted due to the important physical and cognitive growth phase from 0 to 5. Educational institutions can create a stunting prevention forum by incorporating instructors and parents. Parents can discover strategies to meet their children's nutritional demands during this crucial stage. Teachers may mitigate stunting by helping kids live healthy lives. Thus, the Faculty of Economics and Business team from Brawijaya University, Malang, conducts stunting prevention community engagement at an early childhood school. It studies how community participation promotes stunting prevention knowledge among parents and teachers at Raudhatul Qur'an Tahfiz School in Malang. A socialization program at Raudhatul Qur'an Tahfidz School in Malang City aims to raise teachers' and parents' awareness and comprehension of stunting prevention and its prevention methods.